COOLING LOAD AND HEAT TRANSFERS ANALYSIS FOR AIR CONDITIONING SYSTEM OF SUZUKI APV (GC 415) - PERDANA, TUNGGUL DEWA (2011)
The condition of the earth is getting warmer temperature, forcing people to seek various ways to avoid the warm air. Similarly, while driving car, people often felt the warm in the cabin. So, one of solutions to these problems are use Air Conditioning System (A/C) to reduce warm temperature in the cabin. Also, air conditioning can removes moisture in the windshield when driving in rainy. Cooling load calculation includes sensible heats from outdoor and latent heats from indoor. Sensible heats are heat transfers from sunlight through car body to interior cabin. Latent heats are heat transfers from passengers and air vent. Total of heat transfers will produce a total of heat in the car cabin. Then total of heat transfers converted into the power to determine Air Conditioning capacity. Good calculation of cooling load will greatly affect the condition of the room and also used to determine specifications of Air Conditioning components. Suzuki APV uses non frosting evaporator coil with fins, condenser uses air condenser type with finned flat tube and air as a cooling fluid, compressor uses swash plate compressor type, and expansion valve uses thermostatic expansion valve. Exact calculation of cooling load will reduce excessive fuel consumption due to the use of Air Conditioning. Air Conditioning system of Suzuki APV uses basic of vapor compression cycle and R-134a (HFC-134a) as a refrigerant. Total of sensible heat load is 5,687.68 Btu/hr and total of latent heat load is 1,164.11 Btu/hr. So, total of Air Conditioning capacity is 2.69 hp (3 hp rounded). By using refrigerant R-134a, refrigeration system of Suzuki APV has 89 % efficiency.